Regulatory focus and construal level theory on low-income consumer indebtedness: Evidence from an emerging market - Campos, Patrícia de Oliveira; Costa, Marconi Freitas da (International journal of emerging markets, 2023)
PurposeThis study aims to further analyse the decision-making process of low-income consumer from an emerging market by verifying the influence of regulatory focus and construal level theory on indebtedness.Design/methodology/approachAn experimental study was carried out with a design 2 (regulatory focus: promotion vs prevention) × 2 (psychological distance: high vs low) between subjects, with 140 low-income consumers.FindingsOur study points out that the propensity towards indebtedness of low-income consumer is higher in a distal psychological distance. We found that promotion and prevention groups have the same propensity to indebtedness. Moreover, we highlight that low-income consumers are prone to propensity to indebtedness due to taking decisions focused on the present with an abstract mindset.Social implicationsFinancial awareness advertisements should focus on providing more concrete strategies in order to reduce decision-making complexity and provide ways to reduce competing situations that could deplete self-regulation resources. Also, public policy should organize educational programs to increase the low-income consumer's ability to deal with personal finances and reduce this task complexity. Finally, educational financial programs should also incorporate psychology professionals to teach mindfulness techniques applied to financial planning.Originality/valueThis study is the first to consider regulatory focus and construal level to explain low-income indebtedness. This paper provides a deeper analysis of the low-income consumers' decision process. Also, it supports and guides future academic and decision-making efforts.